UMP Global Classroom: Beyond Boundary Learning - Gan, Leong Ming; Adzhar, Kamaludin; Muhammad Azrin, Ahmad; Mohd Shahri, Mohd Akhir; Rosyafieka, Rosli; Nurliyana Najwa, Jamaludin; Shahrul, Mohamed Salleh (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Global Classroom is a contemporary teaching paradigm which is beyond classroom boundary, regardless of geographical, time zone, languages and cultural barriers. This initiative is a form of cybergogy which uses Information and Communication Technology (ICT) to create learner centred, autonomous and collaborative virtual learning environment, so that they can participate and collaborate with peers from other countries. Embedding Global Classroom elements into class activity could provide opportunities for students to boost their understanding of various fields, adapt cross cultural team-working and to help them acquire specific skills in different perspective. Global Classroom is an actively engaged partner program initiated by Centre of Instructional Resources & e-Learning (CIReL) UMP. The main target of Global Classroom is to expand the matrix beyond the conventional physical classroom with the integration of online learning platform, flipped learning, long distance education and simultaneous classroom. UMP Global Classroom is a progressive initiative to embraces globalised online learning (GOL) through basic, standard and advanced modes. The benefits of Global Classroom courses are immense. For many students, such courses are their first or only opportunity to experience direct international communication and interaction. The virtual exchanges at the heart of the courses can act as an alternative to physical mobility or preferably, a supplement to it, either by preparing students for future travel or maintaining previously established connections. The interactions provide opportunities to practice communication skill acquisition while also boosting the student’s levels of intercultural and global competence. For course instructor, Global Classroom also create a global platform to promote and market the niche research and competence skill with international partner which could enhance collaboration in terms of innovation in teaching and learning, research and publication. Finally, they provide a broad platform for engaging student’s digital and media literacy, giving them a chance to develop communication skills that have become a vital element of the social and business world. Since the launching of Global Classroom in UMP in 2016, this initiative are well accepted and quick implementation with simple instructional strategy. Up to date, Global Classroom had engaged UMP with 39 universities from 18 countries and beneficial to more than 1500 students in basic Global Classroom. In next milestone, UMP are moving into standard and advanced Global Classroom to increase the virtual engagement align with substitute blended learning.